Lithium Batteries: Highly Nitridated Graphene–Li2S Cathodes with Stable Modulated Cycles (Adv. Energy Mater. 23/2015). Issue 23 (December 2015) - Qiu, Yongcai; Rong, Genlan; Yang, Jie; Li, Guizhu; Ma, Shuo; Wang, Xinliang; Pan, Zhenghui; Hou, Yuan; Liu, Meinan; Ye, Fangmin; Li, Wanfei; Seh, Zhi Wei; et al.
Abstract : Newly developed in‐situ electron microscopy methods were employed to understand the dissolution processes of the intermediate lithium polysulfides in liquid Li2 S‐C/Li cells by Yi Cui, Yuegang Zhang and co‐workers in article number 1501369. Based on an understanding of the capacity loss mechanism, high‐rate, ultralong cycle‐life Li2 S‐C/Li batteries are demonstrated by combining a highly nitridated graphene–Li2 S cathode with a new charging protocol.